Pengaruh Relationship Marketing, Emotional Branding, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Bank BRI KK Universitas Islam Malang (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Unisma) - Ningrum, Erina Oktavia; Nurhajati, Nurhajati; Basalamah, Muhammad Ridwan (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research endeavors to investigate and clarity the combined effects of relationship marketing, emotional branding, and service quality collectively impact customer satisfaction at Bank BRI KK Islamic University of Malang, focusing on students within the Faculty of Economics and Business at UNISMA. Employing a quantitative methodology, the Maholtra formula is utilized to determine the sample size due to the uncertainty of the population. The calculation yields a sample size of 80. To address the research objectives, SPSS is employed to conduct various tests including validity, normality, and classical assumption tests, as well as hypothesis testing, multiple linear regression analysis, and the adjusted R-squared coefficient of determination test. The findings reveal that relationship marketing, emotional branding, and service quality collectively influence customer satisfaction. Specifically, relationship marketing and service quality partially affect customer satisfaction, whereas emotional branding does not demonstrate a significant impact on customer satisfaction. Keywords: Relationship Marketing, Emotional Branding, Service Quality, Customer Satisfaction